Career path challenges in consultancy sector - Pereira, L.; Diogo Guanilho; Lopes da Costa, R.; Dias, Á.; Gonçalves, R. (International Journal of Learning and Intellectual Capital, 2022)
Careers have been evolving over the years, because of changes in the labour market and individual perspectives and objectives. Nowadays, looking for different working experiences within diverse companies are quite common, and individuals are more concerned about their career progression. In this context, organisations were pushed to learn and adapt their employee value proposition and place a higher focus on individual career needs. In the consultancy sector, career management can be much more complex and difficult to manage for organisations, since consultant’s roles and responsibilities can quickly change. Therefore, this investigation aimed to understand how consultants see the relation between career management, seniority, and performance. The study’s results were based on 92 responses from consultants and former consultants to an online survey and shown that while seniority still has a positive correlation with hierarchical levels, most consultants want to pursue a performance-based career management system, especially the experienced and older ones.